Adversity Quotient di Pesantren - Suheri Suheri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Islamic Boarding school as the oldest institution in Indonesian made a major contribution to the intellectual life of the nation. The great contribution Islamic boarding schools as well as educational, propaganda, social institutions and even a role in the capture, maintain, and develop independence. The long history and its existence is concrete evidence that the boarding school has a strong Adversity Quotient in maintaining its existence. while keeping the values and character in a variety of situations. This paper is a conceptual paper to understand the Adversity Quotient in doing Adversity Learning schools for the students. Adversity Quotient study were found by Paul G. Stolz is a fourth generation quotient indicators in persons after IQ, EQ, SQ. Stolz study initially applied in the business world, then a variety of research and conduct research journals and adopted in schools and colleges. So the study of Adversity Quotient in schools is something the first time in Indonesian. Based on human typology according to Paul G. Stolz found some findings. Quiters Pupils who refuse boarding/learning, Campers Pupils who tried to boarding but failed or did not pass in the education and Pupils Climbers are boarding students who complete education. Adversity Quotien students in the life of the response can be detected early, lifestyle, learning environment, response to change, contributions, language and the ability to face adversity.Keywords: Adversity Quotient, schools, students